Update on terbinafine with a focus on dermatophytoses - Jason G Newland; Susan M Abdel-Rahman (Dove Medical Press, 2009)
Jason G Newland1,3, Susan M Abdel-Rahman2,3Divisions of Infectious Diseases1 and Clinical Pharmacology and Medical Toxicology2, Children’s Mercy Hospitals and Clinics, Kansas City, MO, USA; 3Department of Pediatrics, University of Missouri-Kansas City, School of Medicine, Kansas City, MO, USAAbstract: Since terbinafine was introduced on the world market 17 years ago, it has become the leading antifungal for the treatment of superficial fungal infections, aided by unique pharmacologic and microbiologic profiles. This article reviews mode of action, antimycotic spectrum and disposition profile of terbinafine. It examines the data, accumulated over 15 years, on the comparative efficacy of terbinafine (vs griseofulvin, itraconazole, fluconazole) in the management of the infections for which it is primarily indicated (eg, dermatophytoses) and provides a brief discussion on its use for the treatment of non-dermatophyte infections. Finally, the available data on the newest topical and systemic formulations are introduced.Keywords: tinea, Trichophyton, Microsporum, allylamine, antifungal